Badiuzzaman Said Nursi’s Theology of Resistance: A Postcolonial Reading of Risale-i Nur - Dhita Ayomi Purwaningtyas; Imam Khomaeni Hayatullah; Nindhya Ayomi Delahara (University of Darussalam Gontor, Indonesia, 2025)
This article explores Badiuzzaman Said Nursi's Risale-i Nur as a theological and cultural response to the secularizing project of early Republican Turkey. In a broader postcolonial context, the study examines how Nursi resisted the epistemological and spiritual consequences of Western modernity. The objective is to position Risale-i Nur as a form of decolonial Islamic thought that offers an alternative vision of modernity rooted in Qur'anic metaphysics and ethical spirituality. Using discourse analysis and postcolonial theory—especially Edward Said's Orientalism and Mignolo's epistemic disobedience—this qualitative study interprets Nursi's texts as acts of spiritual resistance. It finds that Nursi's resistance was not political rebellion but an ethical-spiritual struggle that reclaims Islamic knowledge, identity, and reason. Through informal networks (dershanes), educational reform, and ontological reorientation, Risale-i Nur functioned as a counter-hegemonic discourse. The article concludes that Nursi's work represents a constructive Islamic modernity—one that challenges secular paradigms while offering an integrated framework for faith, science, and culture.